2012
DOI: 10.4161/epi.20117
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation and longitudinal pattern of genome-wide DNA methylation from birth to the first two years of life

Abstract: (2012) Individual variation and longitudinal pattern of genome-wide DNA methylation from birth to the first two years of life, Epigenetics, 7:6, 594-605,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 56 publications
10
78
1
Order By: Relevance
“…If the methylome is indeed dynamic throughout life, then differences in DNA methylation profiles in identical twins should increase through life. As expected, studies demonstrate that although within-pair discordances are present from birth, 36 they increase with age, [37][38][39][40][41][42][43][44][45] particularly when twins experience divergent medical histories/ environments. [46][47][48][49] In fact, Novakovic and colleagues 50 found differences during gestation, which increased with gestational age.…”
Section: Introductionsupporting
confidence: 62%
“…If the methylome is indeed dynamic throughout life, then differences in DNA methylation profiles in identical twins should increase through life. As expected, studies demonstrate that although within-pair discordances are present from birth, 36 they increase with age, [37][38][39][40][41][42][43][44][45] particularly when twins experience divergent medical histories/ environments. [46][47][48][49] In fact, Novakovic and colleagues 50 found differences during gestation, which increased with gestational age.…”
Section: Introductionsupporting
confidence: 62%
“…CpGs substantially changed from birth to two years of age 105 and in another study ~8% of the sites on the Illumina arrays showed age-associated methylation in childhood 106 . Multiple studies have demonstrated that some methylation marks show considerable variation over time while others are highly stable 64 96 107 108 .…”
Section: Stability and Inter-individual Variation In Dna Methylationmentioning
confidence: 90%
“…67,68 Our work in the Boston Birth Cohort demonstrated considerable individual variation in DNA methylation, which is detectable at birth and dynamic in the first 2 years, and offered an epigenetic insight into this trans-generational effect. 69 We also found that maternal obesity can alter offspring DNA methylation in multiple genes that may have important implications for future chronic diseases. 70 These findings highlight the presence of in utero mechanisms that are available to respond to nutritional, hormonal, or other metabolic cues by possibly altering the timing and direction of methylation events during fetal development.…”
Section: Epigenetic Mechanismsmentioning
confidence: 68%
“…Developmental programming and the establishment of the epigenome (regulation of gene expression) is most sensitive during the prenatal period. 69 Advances in a wide range of biological, behavioral, and social sciences are expanding our understanding of how early environmental influences and genetic predispositions affect adult diseases. The new science suggests that epigenetic mechanisms could be an important interface that links genetic factors, environmental factors, and phenotypic expression.…”
Section: The Need For Future Researchmentioning
confidence: 99%